Impact of pulmonary hypertension on outcomes after transcatheter tricuspid valve edge-to-edge repair - Stolz, Lukas; Kresoja, Karl-Patrik; von Stein, Jennifer; Fortmeier, Vera; Koell, Benedikt; Rottbauer, Wolfgang; Kassar, Mohammad; Goebel, Bjoern; Denti, Paolo; Achouh, Paul; Rassaf, Tienush; Barreiro-Perez, Manuel; et al. (JACC Cardiovascular interventions, 2025)
Background - Data regarding the association of pulmonary hypertension (PH) and outcomes in patients undergoing transcatheter tricuspid valve edge-to-edge repair (T-TEER) are scarce. - Objectives - The aims of this study were: 1) to investigate the impact of PH on outcomes after T-TEER; and 2) to shed further light on the role of precapillary- and postcapillary PH in patients undergoing T-TEER for relevant tricuspid regurgitation (TR). - Methods - The study included patients from EuroTR (European Registry of Transcatheter Repair for Tricuspid Regurgitation; NCT06307262) who underwent T-TEER for relevant TR from 2016 until 2023 with available invasive evaluation of systolic pulmonary artery pressure (sPAP) using right heart catheterization. Study endpoints were procedural TR reduction, improvement in NYHA function class, and a combined endpoint of death or heart failure hospitalization (HFH) at 2 years. - Results - Among a total of 1,230 patients (mean age 78.6 ± 7.0 years, 51.4% women), increasing sPAP was independently associated with increasing rates of 2-year death or HFH (HR: 1.027; 95% CI: 1.003-1.052; P = 0.030; median survival follow-up 343 days [Q1-Q3: 114-645 days]). No significant survival differences were observed for patients with pre- vs postcapillary PH. Sensitivity analysis revealed an sPAP value of 46 mm Hg as the optimized threshold for the prediction of death or HFH. Being observed in 526 patients (42.8%), elevated sPAP (>46 mm Hg) was associated with more severe heart failure symptoms at baseline and follow-up. Importantly, NYHA functional class significantly improved and TR severity was significantly reduced irrespective of PH. - Conclusions - PH is an important outcome predictor in patients undergoing T-TEER for relevant TR. In contrast to previous studies, no significant differences were observed for patients with precapillary and postcapillary PH in terms of survival free from HFH.
EuroTR Investigators: Roman Pfister, Martin Kraus [und 28 weitere Personen]
Online veröffentlicht: 28. Oktober 2024, Artikelversion: 10. Februar 2025
Gesehen am 08.12.2025